2018
DOI: 10.1080/14737167.2018.1517046
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the cancer-specific QLQ-C30 onto the generic EQ-5D-5L and SF-6D in colorectal cancer patients

Abstract: Our results demonstrated that algorithms developed based on OLS Models 1 and 2 are the best for predicted EQ-5D-5L and SF-6D values respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…20 The CLAD model is another alternative that estimates coefficients based on median. 21 Nevertheless, the CLAD is not appropriate because the most econometric models are based on the mean, and some evidence shows that it performed poorly in studies that had used the EQ-5D instrument as the dependent variable. 22,23 One of the efforts to overcome these problems is using the estimators based on the beta distribution.…”
Section: Discussionmentioning
confidence: 99%
“…20 The CLAD model is another alternative that estimates coefficients based on median. 21 Nevertheless, the CLAD is not appropriate because the most econometric models are based on the mean, and some evidence shows that it performed poorly in studies that had used the EQ-5D instrument as the dependent variable. 22,23 One of the efforts to overcome these problems is using the estimators based on the beta distribution.…”
Section: Discussionmentioning
confidence: 99%
“…14 Utility values obtained from the Euro QoL EQ-5D-5L Persian version. 15 Patients asked about their current condition and their condition during states. The utility data of HD, PD, and TX patients, was 0.72 and 0.75, and 0.82 respectively.…”
Section: Research Methods and Patients Descriptionsmentioning
confidence: 99%
“…Among them, numerical algorithms have been developed to map disease-specific questionnaires to the EuroQol Group Five-Dimensional (EQ-5D), a standardized instrument for measuring generic health status, values in cancer groups. [11][12][13][14] The EQ-5D is one of the most commonly used instruments to describe and assess HRQoL based on public preference; it has two versions: the 3 level (3L) and 5 level (5L). 15 A study using a sizeable multinational dataset showed that, compared with the 3L, the 5L is more accurate and preferred regarding both study results and participant responses.…”
Section: Introductionmentioning
confidence: 99%